2022
DOI: 10.1109/access.2022.3152828
|View full text |Cite
|
Sign up to set email alerts
|

RoBERTa-LSTM: A Hybrid Model for Sentiment Analysis With Transformer and Recurrent Neural Network

Abstract: Due to the rapid development of technology, social media has become more and more common in human daily life. Social media is a platform for people to express their feelings, feedback, and opinions. To understand the sentiment context of the text, sentiment analysis plays the role to determine whether the sentiment of the text is positive, negative, neutral or any other personal feeling. Sentiment analysis is prominent from the perspective of business or politics where it highly impacts the strategic decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(39 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…In this paper, in addition to the BERT model, we propose more improved models of BERT, which are robustly optimized BERT pre-training approach (RoBERTa) and DistilBERT. RoBERTa [29]- [31] is improved by removing next sentence prediction during training and giving dynamic masking that will keep changing, longer training time will go with larger batch sizes. RoBERTa is proposed to improve the accuracy of the BERT model.…”
Section: Research Methods 21 Related Algorithmsmentioning
confidence: 99%
“…In this paper, in addition to the BERT model, we propose more improved models of BERT, which are robustly optimized BERT pre-training approach (RoBERTa) and DistilBERT. RoBERTa [29]- [31] is improved by removing next sentence prediction during training and giving dynamic masking that will keep changing, longer training time will go with larger batch sizes. RoBERTa is proposed to improve the accuracy of the BERT model.…”
Section: Research Methods 21 Related Algorithmsmentioning
confidence: 99%
“…The authors of [32] employed topic modelling and sentiment analysis on tweets regarding global climate change to reveal public opinion. The authors of [36] used "IMDB", "Twitter-US-Airline-Sentiment", and "Sentiment140" datasets, and "Roberta-LSTM" outperforms state-of-the-art sentiment analysis algorithms. The paper's contributions are threefold:…”
Section: Related Workmentioning
confidence: 99%
“…A hybrid deep learning method is proposed by [21] and has concluded that RoBERTa-LSTM model benefits from the strengths of both RoBERTa and LSTM, where RoBERTa efficiently encodes the words into word embedding while LSTM excels in capturing the long-distance dependencies…”
Section: Related Workmentioning
confidence: 99%